Odpowiedź :
Odpowiedź:
x = 10100
Szczegółowe wyjaśnienie:
2*[tex]10^{6}[/tex] * x + 3,8 * [tex]10^{9}[/tex] = 2,4 * [tex]10^{10}[/tex] /:[tex]10^{6}[/tex]
2*x + 3,8 * [tex]10^{3}[/tex] = 2,4 * [tex]10^{4}[/tex]
2x + 3800 = 24000
2x = 24000 - 3800
2x = 20200 /:2
x = 10100
[tex](2\cdot10^{6})\cdot x + 3,8\cdot10^{9} = 2,4\cdot10^{10}\\\\2\cdot10^{6}x = 2,4\cdot10^{10} -3,8\cdot10^{9}\\\\2\cdot10x = 24\cdot10^{9}-3,8\cdot10^{9}\\\\2\cdot10^{6}x = (24-3.8)\cdot10^{9}\\\\2\cdot10^{6}x = 20,2\cdot10^{9} \ \ /:(2\cdot10^{6})\\\\x = 10,1\cdot10^{3}\\\\\boxed{x = 10 \ 100}[/tex]